2006
DOI: 10.2136/sssaj2006.0051
|View full text |Cite
|
Sign up to set email alerts
|

Speciation and Distribution of Phosphorus in a Fertilized Soil

Abstract: Phosphorus availability is often a limiting factor for crop production around the world. The efficiency of P fertilizers in calcareous soils is limited by reactions that decrease P availability; however, fluid fertilizers have recently been shown, in highly calcareous soils of southern Australia, to be more efficient for crop (wheat [Triticum aestivum L.]) P nutrition than granular products. To elucidate the mechanisms responsible for this differential response, an isotopic dilution technique (E value) coupled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
1
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(91 citation statements)
references
References 33 publications
5
77
1
6
Order By: Relevance
“…Sulfur L-edge NEXAFS spectroscopy could provide complementary information to identify these sulfur moieties (Kasrai et al, 1996), but this technique only works well for samples that have large amounts of sulfur such as in coal (M. Kasrai, personal communication), and our attempt to resolve the organic sulfur species in humic substance extracts using S L-edge NEXAFS spectroscopy did not provide satisfactory results (D. Solomon, unpublished data 2005). While NEXAFS studies of organic phosphorus are rare (Toor et al, 2005;Sato et al, 2005), Beauchemin et al (2003) and Lombi et al (2006) demonstrated that P K-edge spectroscopy has great potential to investigate inorganic phosphorus species in long-term-fertilized, P-rich soils differing in pH, clay, and organic matter. In an experiment conducted in conjunction with wet chemical techniques to characterize the dominant solid-phase species of phosphorus, Beauchemin et al (2003) also showed that the results obtained by NEXAFS spectroscopy for calcium (r = 0.87)-related and aluminum or iron (r = 0.99)-related phosphorus species correlated very well with the HCl extractable and NaOH extractable inorganic phosphorus species obtained from sequential phosphorus fractionation technique, respectively.…”
Section: Relationship With Other Methodsmentioning
confidence: 99%
“…Sulfur L-edge NEXAFS spectroscopy could provide complementary information to identify these sulfur moieties (Kasrai et al, 1996), but this technique only works well for samples that have large amounts of sulfur such as in coal (M. Kasrai, personal communication), and our attempt to resolve the organic sulfur species in humic substance extracts using S L-edge NEXAFS spectroscopy did not provide satisfactory results (D. Solomon, unpublished data 2005). While NEXAFS studies of organic phosphorus are rare (Toor et al, 2005;Sato et al, 2005), Beauchemin et al (2003) and Lombi et al (2006) demonstrated that P K-edge spectroscopy has great potential to investigate inorganic phosphorus species in long-term-fertilized, P-rich soils differing in pH, clay, and organic matter. In an experiment conducted in conjunction with wet chemical techniques to characterize the dominant solid-phase species of phosphorus, Beauchemin et al (2003) also showed that the results obtained by NEXAFS spectroscopy for calcium (r = 0.87)-related and aluminum or iron (r = 0.99)-related phosphorus species correlated very well with the HCl extractable and NaOH extractable inorganic phosphorus species obtained from sequential phosphorus fractionation technique, respectively.…”
Section: Relationship With Other Methodsmentioning
confidence: 99%
“…Aluminum phosphate minerals are characterized by weak pre-edge inflection at about 2148 eV. These spectral features of phosphate bond with Ca, Al, and Fe and have been well documented Peak et al, 2002;Beauchemin et al, 2003;Khare et al, 2005;Lombi et al, 2006), which helps us determine the association of phosphate with different elements in soil samples.…”
Section: X-ray Absorption Near Edge Structure Analysismentioning
confidence: 93%
“…In 62% of the P-responsive soils, wheat dry matter was significantly greater when liquid P fertilizers (phosphoric acid and ammonium polyphosphate) were used compared with the granular form (triple superphosphate), and they related this result to calcium carbonate content of the soils. The superior performance of liquid P was attributed to the greater outward diffusion of liquid P from the point of placement compared with granular P, thus reducing the chances of creating microenvironment soil solutions supersaturated with various solid Ca-P species (Lombi et al, 2004;Hettiarachchi et al, 2006;Lombi et al, 2006). We hypothesized that this enhanced or greater P diffusion would be beneficial for reduced-tillage systems, and that surface or deep-banded liquid P fertilizers may be a suitable alternative for reduced-tillage systems.…”
Section: Speciation Of Phosphorus In a Fertilized Reduced-tillmentioning
confidence: 99%
See 1 more Smart Citation
“…To succeed, theorists with statistical and modeling expertise must have good data available, and these results must be connected to standard measurements in other, as well as similar, systems. The phosphorus depletion or enhancement in agricultural soils is one example (16).…”
Section: Advantages Of Combining Microscopy and Spectroscopymentioning
confidence: 99%